Electronic Properties of Topological Superconductors XC (X = V, Nb) with Hexagonal Structure: A Density Functional Theory Perspective - Erik Bhekti Yutomo; Suci Faniandari; Oki Ade Putra (BULETIN FISIKA, 2025)
Topological superconductors are a class of materials that combine superconductivity with nontrivial topological electronic band structures. In this study, we investigate the electronic properties of two transition metal carbides, VC and NbC, in their hexagonal phases. The calculations are performed using the Density Functional Theory (DFT) approach, with explicit consideration of spin–orbit coupling (SOC) to explore the possible emergence of nontrivial band topology. The calculated band structures reveal metallic behavior in both materials, characterized by the presence of electronic states at the Fermi level. VC exhibits two Dirac points along the Γ–M and K–Γ paths, as well as a Weyl point at the K point. In contrast, NbC shows two Dirac points and one triply degenerate point along the Γ–A path. Upon inclusion of SOC, these topological features not only persist but become more pronounced, particularly near the K point and along the Γ–A direction. The projected density of states (PDOS) analysis indicates that these topological features originate from strong hybridization between the transition metal d orbitals (V 3d and Nb 4d) and the carbon 2p orbitals. These results suggest that hexagonal-phase VC and NbC are promising candidates for topological superconductors, with potential applications in future quantum technologies.